Estimation of heavy metals toxicity in the groundwater of rural area near Ellenabad, Sirsa (Haryana) - Kumar, Parul; Jain, Sushma (E3S web of conferences, 2023)
The present investigation emphasizes on the evaluation of heavy metal pollution indices to assess the suitability of groundwater for human consumption. For this, thirty groundwater samples were collected from the villages near Ellenabad city of Sirsa during pre monsoon of 2018 from the tube-wells. The samples were collected from approximately 100 m of depth. The samples were analyzed using Inductively Coupled Plasma – Mass Spectrometry (ICP - MS) for heavy metals like As, Hg, Pb, Zn, Cu and Mn. The heavy metals As, Hg and Pb were not found in our samples. The indices like heavy metal pollution index (HPI), heavy metal evolution index (HEI) and Hazard index (HI) were calculated to assess the suitability for drinking. These indices numerically give the suitability of groundwater for human consumption. On the basis of HEI and HPI, all the samples were found to be suitable for human consumption. The value of HI > 1 shows the unsuitability of groundwater for consumption. On the basis of the analysis, it can be said that children are at more risk followed by adults and then infants. The value of HI > 1 has been found for only two samples and which was also for children in sample number 20 and 24. So, majority of the samples have been found to be suitable for human consumption. Principal component analysis was performed for factor analysis which shows the initial Eigen value of more than two and total variance of more than 41.